A correlational study on organizational culture and leadership style - Jemar B. Abenoja; Dhamian John C. Blase; Ronald E. Almagro (Annals of Management and Organization Research, 2025)
Purpose: This study aimed to explore the relationship between organizational culture and leadership styles among Local Government Unit (LGU) departments in the municipality of Santo Tomas, Davao del Norte. Research Methodology: Prior to data collection, the respondents were presented with a letter requesting their cooperation in completing the questionnaires. The researchers personally introduced themselves, explained the study objectives, and distributed questionnaires. After providing sufficient time for respondents to complete the questionnaires, they were collected. Results: Results revealed that the independent variable, Organizational Culture, had a mean score of 4.45, which was interpreted as "very high," while the dependent variable, Leadership Style, had a mean score of 4.51, also categorized as "very high." Furthermore, the overall correlation coefficient (r-value) was 0.573, with a p-value of 0.001, leading to rejection of the null hypothesis. This indicates a significant and positive relationship between Organizational Culture and Leadership Style in the LGU departments of Santo Tomas, Davao del Norte. The findings suggest that a stronger organizational culture positively influences leadership style, with higher levels of culture leading to enhanced leadership behaviors. Conclusions: Overall, the findings show that organizational culture and leadership style are both rated extremely high, with a significant and strong positive relationship between them, leading to the rejection of the null hypothesis. Limitations: This study is limited by its focus on a single municipality and the use of universal sampling, which may restrict the generalizability of the findings to other contexts or organizations. Contribution:  This study offers valuable insights into local government units and organizational development, highlighting the importance of fostering a strong organizational culture to enhance leadership practices and organizational success.